Case Report: Clinical Characteristics and Outcomes of HIV Positive Patients With Metastatic Prostate Cancer Treated With Immunotherapy: A Case Series and Literature Review - Idossa, Dame; Friedlander, Terence; Paller, Channing J.; Ryan, Charles J.; Borno, Hala T. (Frontiers in Oncology, 2022)
Background: The treatment of metastatic prostate cancer has been revolutionized with the advent of many targeted therapies, including immunotherapy. Pembrolizumab has demonstrated benefit in the treatment of certain patients with docetaxel-refractory metastatic castrate-resistant prostate cancer (mCRPC). However, extrapolation of these data to patients with HIV is limited, as these patients are conventionally excluded from therapeutic clinical trials. This study aims to develop a better understanding of the clinical outcomes of HIV positive patients with prostate cancer treated with immunotherapy. A review of the literature is conducted on the use of immunotherapy in HIV positive patients with prostate cancer, and a summary is presented of two clinical cases from a single institution. Methods: This is a retrospective case report of 2 patients diagnosed with prostate cancer and HIV who received treatment with pembrolizumab. Quantitative analysis was performed to summarize patient demographics, clinical history, and outcomes. Results: Two patients with mCRPC and HIV on highly active antiretroviral therapy were identified. Both individuals had biochemical and radiographic response to treatment with pembrolizumab. The duration of response for individual 1 is >31 months and 14 months for individual 2. Neither patient had immune-related adverse events or decreased suppression of their HIV infection. One patient died from disease progression after 14 months of treatment and the other remains on treatment with pembrolizumab to date. Conclusion: In this small case series, pembrolizumab appears to be a safe and effective treatment option for HIV positive patients with metastatic prostate cancer.